2013
DOI: 10.1002/jat.2873
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in blood genotoxic and cytotoxic effects as a consequence of vanadium inhalation: micronucleus assay evaluation

Abstract: Vanadium is an environmental pollutant attached to the smallest air suspended particles that enters into the respiratory tract reaching the systemic circulation. The oxidative state of this element and sex are factors related to its toxicity. In this study, we explored sex-associated genotoxic and cytotoxic differences in a mouse experimental model. Mice inhaled V2O5 (0.02 M) 2 h/twice a week; blood samples were obtained at 24 h and every week until the end of the 4-week exposure. Samples were processed for fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…In a previous study, we observed that the frequency of micronuclei in polychromatic erythrocytes (MN-PCE) increased with the administration of 40 mg/kg of V 2 O 5 through ip [8], consistent with other studies testing soluble vanadium compounds (Na 3 VO 4 , SVO 5, and NH 4 VO 3 ) [34][35][36]. However, the in vivo administration of vitamin C prior to the V 2 O 5 injection decreased MN-PCE formation compared to administering V 2 O 5 alone, reducing basal MN-PCE, and presenting the strongest protection against genotoxic damage induced by V 2 O 5 .…”
Section: Protective Efects Of Vitamin C Against Genotoxic Damage Fromsupporting
confidence: 90%
“…In a previous study, we observed that the frequency of micronuclei in polychromatic erythrocytes (MN-PCE) increased with the administration of 40 mg/kg of V 2 O 5 through ip [8], consistent with other studies testing soluble vanadium compounds (Na 3 VO 4 , SVO 5, and NH 4 VO 3 ) [34][35][36]. However, the in vivo administration of vitamin C prior to the V 2 O 5 injection decreased MN-PCE formation compared to administering V 2 O 5 alone, reducing basal MN-PCE, and presenting the strongest protection against genotoxic damage induced by V 2 O 5 .…”
Section: Protective Efects Of Vitamin C Against Genotoxic Damage Fromsupporting
confidence: 90%
“…However, recent studies reported a slight increase in 8-oxodGuo DNA lesions in lungs of female B 6 C 3 F 1 mice exposed to 1 or 4 mg/m 3 V 2 O 5 for 16 days by nose-only inhalation [21], and increased micronuclei in peripheral blood in male but not female CD1 mice exposed to 1.4 mg/m 3 V 2 O 5 for 2 h per week for 4 weeks by aerosol inhalation [20]. 8-oxodGuo DNA lesions are likely to be mutagenic, and impaired or defective repair of these lesions can induce mostly G → T and A → C transversions [22,27], which can be detected in lungs of BB mice following exposure to V 2 O 5 .…”
Section: Discussionmentioning
confidence: 96%
“…In CD1 mice, intraperitoneal administration of V 2 O 5 induced significant DNA damage in multiple tissues, such as lung, heart, liver, bone marrow, spleen, and kidney, as measured by the alkaline comet assay 24 h following the treatment, but the increase was not concentration-dependent [19]. Recently, the same authors exposed male and female CD1 mice to 1.4 mg/m 3 V 2 O 5 for 2 h per week for 4 weeks by aerosol inhalation and reported a significant induction of micronucleus frequency in the peripheral blood only in males [20]. Although toxic exposure levels were reached in both males and females, as evidenced by the significant decrease in reticulocytes seen in both sexes, the absence of genotoxic effects in the female mice was attributed to the protective effect against oxidative stress conferred by their higher estrogen levels.…”
Section: Introductionmentioning
confidence: 94%
“…Information related to the carcinogenic and genotoxic potential of vanadium pentoxide (V 2 O 5 ) is limited [14]. In both animal and human models, the effects on the DNA caused by vanadium include single strand breaks, micronuclei, chromosomal aberrations (structural and numerical), and oxidation of nitrogenous bases [15,16]. The spectrum of alterations that DNA might have as a consequence of free radicals interaction, in this case caused by vanadium, are: deoxyribose oxidation, modification of nitrogen bases, chain cross-linking, and ruptures [6].…”
Section: Oxidative Stress Vanadium and Dna Damagementioning
confidence: 99%